Green synthesis of silver nanoparticles using leaf and stem bark extract of Pometia pinnata J.R. Forst & G. Forst. Issue 1 (March 2020) - Ningrum, A S; Pridyantari, A P; Handayani, W; Secario, K; Djuhana, D; Imawan, C
Abstract: Pometia pinnata (Matoa) is widely known for its use in traditional medicines and as fruit sources in Indonesia. Stem bark and leaves of Matoa are the most used parts. Each part contains secondary metabolites, including flavonoids, tannins, triterpenoids, glycosides, and saponins. These compounds could act as reducing agents in the biosynthesis of silver nanoparticles. Our research attempts to compare the efficacy of aqueous extracts of Matoa leaf and stem bark in the biosynthesis of silver nanoparticles. We characterized products of silver nanoparticles using UV-Vis spectrophotometer, transmission electron microscope, and particle size analyzer to compare the biosynthesis between the two parts based on ratios of various concentrations of plant extract to silver nitrate (AgNO3). We found that the solution (extract and AgNO3) became darker as the concentration and reaction time increased. Increasing reaction time also caused an increase in absorption peak intensity due to the reduction process of silver ions. The use of leaf and stem bark for biosynthesis resulted in different shapes and sizes of silver nanoparticles; the use of leaves and stem bark resulted in sphere-shaped silver nanoparticles, whereas the use of aqueous leaf extracts triangle-shaped silver nanoparticles formed.